Comparison of parasite species and burden between apparently healthy and clinically ill Red Jungle Fowl, Gallus gallus gallus - Zaini, Zati Hidayah (2016)
The Red Jungle Fowl, Gallus gallus is one of the four species of jungle fowl found in Asia. It is known as the ancestor of the domestic fowl (Gallus domesticus) due to its widespread distribution. These birds when domesticated were observed to be very susceptible to the diseases affecting the domestic chickens. As there are only few studies conducted on the Red Jungle Fowl species especially comparing the parasite flora of healthy and sick birds, therefore this study is aimed to identify the ectoparasites, endoparasites and blood parasites harboured by the apparently healthy and clinically ill Red Jungle Fowl and to compare the burden of the parasites between these two groups. 12 clinically ill (those showing clinical symptoms) and four apparently healthy Red Jungle Fowl were sampled from a Red Jungle Fowl farm located at Jenderam Hulu, Selangor. The birds were examined for ectoparasites, endoparasites and blood parasites. The species of parasites recovered included Haemaphysalis wellingtoni, Lipeurus caponis, Menopon gallinae, Menacanthus stramineus, Goniodes dissimilis, Goniocotes hologaster (ectoparasites); Strongeloides sp., Capillaria sp., Heterakis gallinarum, Raillietina cesticillus, Raillietina tetragona, Raillietina echinobothridia, Eimeria sp., (endoparasites); Plasmodium gallinaceum, Leucocytozoon sabrazesi, Microfilaria sp., Trypanosome sp.(blood parasites). The results showed that there were no significant differences between burden of parasite species in apparently healthy and clinically ill Red Jungle Fowls except only for the lice, Lipeurus caponis. In conclusion, generally, the apparently healthy and clinically ill Red Jungle Fowls have the same species and burden of parasites harbouring them. Some other organisms, probably bacteria or viruses may be causing the disease in clinically affected birds.